Survival of offspring who experience early parental death: Early life conditions and later-life mortality - Smith, Ken R. (2014)
We examine the influences of a set of early life conditions (ELCs) on all-cause and cause-specific mortality among elderly individuals, with special attention to one of the most dramatic early events in a child’s, adolescent’s, or even young adult’s life, the death of a parent. The foremost question is, once controlling for prevailing (and potentially confounding) conditions early in life (family history of longevity, paternal characteristics (SES, age at time of birth, sibship size, and religious affiliation)), is a parental death associated with enduring mortality risks after age 65? The years following parental death may initiate new circumstances through which the adverse effects of paternal death operate. Here we consider the offspring’s marital status (whether married; whether and when widowed), adult socioeconomic status, fertility, and later life health status. Adult health status is based on the Charlson Co-Morbidity Index, a construct that summarizes nearly all serious illnesses afflicting older individuals that relies on Medicare data. The data are based on linkages between the Utah Population Database and Medicare claims that hold medical diagnoses data. We show that offspring whose parents died when they were children, but especially when they were adolescents/young adults, have modest but significant mortality risks after age 65. What are striking are the weak mediating influences of later-life comorbidities, marital status, fertility and adult socioeconomic status since controls for these do little to alter the overall association. No beneficial effects of the surviving parent’s remarriage were detected. Overall, we show the persistence of the effects of early life loss on later-life mortality and indicate the difficulties in addressing challenges at young ages.